Cryo-EM structures of a human ABCG2 mutant trapped in ATP-bound and substrate-bound states. (15th November 2018) - Manolaridis, Ioannis; Jackson, Scott; Taylor, Nicholas; Kowal, Julia; Stahlberg, Henning; Locher, Kaspar
Abstract ABCG2 is a transporter protein of the ATP-binding-cassette (ABC) family that is expressed in the plasma membrane in cells of various tissues and tissue barriers, including the blood–brain, blood–testis and maternal–fetal barriers1–4 . Powered by ATP, it translocates endogenous substrates, affects the pharmacokinetics of many drugs and protects against a wide array of xenobiotics, including anti-cancer drugs5–12 . Previous studies have revealed the architecture of ABCG2 and the structural basis of its inhibition by small molecules and antibodies13, 14 . However, the mechanisms of substrate recognition and ATP-driven transport are unknown. Here we present high-resolution cryo-electron microscopy (cryo-EM) structures of human ABCG2 in a substrate-bound pre-translocation state and an ATP-bound post-translocation state. For both structures, we used a mutant containing a glutamine replacing the catalytic glutamate (ABCG2EQ ), which resulted in reduced ATPase and transport rates and facilitated conformational trapping for structural studies. In the substrate-bound state, a single molecule of estrone-3-sulfate (E1 S) is bound in a central, hydrophobic and cytoplasm-facing cavity about halfway across the membrane. Only one molecule of E1 S can bind in the observed binding mode. In the ATP-bound state, the substrate-binding cavity has collapsed while an external cavity has opened to the extracellular side of the membrane. The ATP-induced conformational changes include rigid-body shifts of the transmembrane domains, pivoting of the nucleotide-binding domains (NBDs), and a change in the relative orientation of the NBD subdomains. Mutagenesis and in vitro characterization of transport and ATPase activities demonstrate the roles of specific residues in substrate recognition, including a leucine residue that forms a 'plug' between the two cavities. Our results show how ABCG2 harnesses the energy of ATP binding to extrude E1 S and other substrates, and suggest that the size and binding affinity of compounds are important for distinguishing substrates from inhibitors. Cryo-electron microscopy structures of the ABCG2 protein in ATP- and substrate-bound states reveal the location of substrate binding, conformational changes required for substrate translocation and how inhibitors might be distinguished from substrates.